State-of-the-art review and design of grouted duct connections for precast bridge columns. (April 2021) - Tazarv, Mostafa; Shrestha, Grishma; Saiidi, M. Saiid
Abstract: The use of prefabricated bridge columns in seismic regions is challenging since performance data on precast column connections is limited. A handful accelerated bridge construction (ABC) details to connect precast columns to adjoining members have been experimentally investigated, and some were found viable for seismic applications and field deployment. A connection consisting of ducts filled with conventional grout is the focus of the present study. In this connection type, precast column longitudinal bars are protruded out of the column and are inserted into grout-filled ducts matching the number and configuration of the column bars. A state-of-the-art review of the grouted duct connection studies and bridge component tests utilizing this connection type is presented. A preliminary design equation for duct connection filled with conventional grout is proposed based on the data collected from the literature. Subsequently, the validity of this equation is evaluated through pullout testing of 12 full-scale grouted-duct specimens. Finally, a refined design equation is proposed based on all available test data, and construction guidelines are developed to facilitate the use of grouted duct ABC column connections in high seismic regions. These design and construction guidelines were proposed to the American Association of State Highway and Transportation Officials (AASHTO) for possible adoption as national specifications.